Imperfect self-knowledge about skills and skill mismatch - Goller, Daniel [Verfasser]; Brox, Enzo [Verfasser]; Wolter, Stefan C. [Verfasser] (My University, 2026)
„Why do people sort into poorly fitting occupations? This paper shows that imperfect self-knowledge about skills is an important source of skill mismatch at labor market entry. We use unique data from standardized professional aptitude tests linked to administrative records on educational trajectories and early labor market outcomes in Switzerland. The data allow us to observe objective skills and subjective skill beliefs for many productivity-relevant skills in a high-stakes setting. We document large differences among individuals in how well their beliefs align with their skills. Imperfect self-knowledge predicts misaligned occupational aspirations, higher realized skill mismatch, and a higher probability of dropout. Guided by a Roy-style model of occupational choice with imperfect self-knowledge, we interpret these findings as evidence that distorted self-assessments at the school-to-work transition contribute to the misallocation of talent.“ (authors‘ abstract; BIBB-Doku)

„Warum wählen junge Menschen Berufe, die nicht zu ihren Fähigkeiten passen? Diese Frage hat eine Studie der Universität Bern anhand von Kompetenztests und Selbsteinschätzungen von 25'000 Jugendlichen in der Schweiz untersucht. Das Resultat: Wer seine Fähigkeiten falsch einschätzt, entwickelt häufiger Berufswünsche, die nicht zu den tatsächlichen Kompetenzen passen. Rückmeldungen zu den Kompetenzen helfen einigen Jugendlichen, viele halten jedoch an ihren ursprünglichen Berufswünschen fest. Die Studie zeigt zudem, dass eine Diskrepanz zwischen den Anforderungen eines Berufs und den vorhandenen Fähigkeiten das Risiko eines Lehrabbruchs deutlich erhöht. Die Daten für die Studie stammen von der Gateway Solutions AG.“ (BIBB-Doku)
Keywords: P 1.1 Jugendliche; L 5 Beratung & Orientierung; 370; Jugendlicher; Berufswahl; Berufswahlverhalten; Kompetenz; Kompetenzdiagnostik; Kompetenzbewertung; Selbsteinschätzung; Schweiz